A nano-scaled and multi-layered recombinant fibronectin/cadherin chimera composite selectively concentrates osteogenesis-related cells and factors to aid bone repair. (15th April 2017) - Xing, Junchao; Mei, Tieniu; Luo, Keyu; Li, Zhiqiang; Yang, Aijun; Li, Zhilin; Xie, Zhao; Zhang, Zehua; Dong, Shiwu; Hou, Tianyong; Xu, Jianzhong; Luo, Fei
Graphical abstract: Abstract: Easily accessible and effective bone grafts are in urgent need in clinic. The selective cell retention (SCR) strategy, by which osteogenesis-related cells and factors are enriched from bone marrow into bio-scaffolds, holds great promise. However, the retention efficacy is limited by the relatively low densities of osteogenesis-related cells and factors in marrow; in addition, a lack of satisfactory surface modifiers for scaffolds further exacerbates the dilemma. To address this issue, a multi-layered construct consisting of a recombinant fibronectin/cadherin chimera was established via a layer-by-layer self-assembly technique (LBL-rFN/CDH) and used to modify demineralised bone matrix (DBM) scaffolds. The modification was proven stable and effective. By the mechanisms of physical interception and more importantly, chemical recognition (fibronectin/integrins), the LBL-rFN/CDH modification significantly improved the retention efficacy and selectivity for osteogenesis-related cells, e.g., monocytes, mesenchymal stem cells (MSCs) and hematopoietic stem cells (HSCs), and bioactive factors, e.g., bFGF, BMP-2 and SDF-1α. Moreover, the resulting composite (designated as DBM-LBL-rFN/CDH) not only exhibited a strong MSC-recruiting capacity after SCR, but also provided favourable microenvironments for the proliferation and osteogenic differentiation of MSCs. Eventually, bone repair was evidently improved. Collectively, DBM-LBL-rFN/CDH presented a suitable biomaterial for SCR and a promising solution for tremendous need for bone grafts. Statement of Significance: There is an urgent need for effective bone grafts. With the potential of integrating osteogenicity, osteoinductivity and osteoconductivity, selective cell retention (SCR) technology brings hope for developing ideal grafts. However, it is constrained by low efficacy and selectivity. Thus, we modified demineralized bone matrix with nano-scaled and multi-layered recombinant fibronectin/cadherin chimera (DBM-rFN/CDH-LBL), and evaluate its effects on SCR and bone repair. DBM-rFN/CDH-LBL significantly improved the efficacy and selectivity of SCR via physical interception and chemical recognition. The post-enriched DBM-rFN/CDH-LBL provided favourable microenvironments to facilitate the migration, proliferation and osteogenic differentiation of MSCs, thus accelerating bone repair. Conclusively, DBM-rFN/CDH-LBL presents a novel biomaterial with advantages including high cost-effectiveness, more convenience for storage and transport and can be rapidly constructed intraoperatively.